2020
DOI: 10.3390/ijms21197034
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of STAT1 and STAT3 Signaling

Abstract: STAT1 and STAT3 are nuclear transcription factors that regulate genes involved in cell cycle, cell survival and immune response. The cross-talk between these signaling pathways determines how cells integrate the environmental signals received ultimately translating them in transcriptional regulation of specific sets of genes. Despite being activated downstream of common cytokine and growth factors, STAT1 and STAT3 play essentially antagonistic roles and the disruption of their balance directs cells from surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 90 publications
4
57
0
Order By: Relevance
“…p value 0.04). Stat3 is phosphorylated and translocated into the nucleus (Figure 5A–C ), despite potential redox interference in Stat3 phosphorylation 67 by increased amounts of Xdh. In addition, mRNA encoding Timp1, which suppresses matrix degradation is increased almost twofold (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…p value 0.04). Stat3 is phosphorylated and translocated into the nucleus (Figure 5A–C ), despite potential redox interference in Stat3 phosphorylation 67 by increased amounts of Xdh. In addition, mRNA encoding Timp1, which suppresses matrix degradation is increased almost twofold (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…STAT1 and STAT3 are not only significantly up-regulated, but also have more binding sites ( STAT1:6 , STAT3:7 ) at the promoter region of Mb in our results. STAT1 and STAT3 are signal transducers and transcriptional activators that play an important role in regulating cell proliferation, differentiation and migration [ 39 , 40 ]. Grohmann and others have shown that oxidative stress caused by obesity inhibits the activity of protein tyrosine phosphatase and leads to the activation of STAT1 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…# p < .01, as compared to the cells exposed to PM alone. HGFs, human gingival fibroblasts; PM, particulate matter also a redox-sensitive protein 38. Hence, this study supposed that STAT1 can be a crucial node linking ROS signaling pathway and VCAM-1 expression in HGFs, leading to monocyte adhesion.…”
mentioning
confidence: 82%